THE INSTITUTE OF PRESIDENCY IN UKRAINE AS A COMPONENT OF THE SYSTEM OF REGULATION GOVERNMENT AND BUSINESS RELATIONS - Zaidel, М. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
The article deals with the problem of the institute of presidency in the system of regulation government and business relations. It is underlined that the president’s authority depends on the alignment of forces of key big business agents and their political power. The problem of constitutional settlement of the institute of presidency is explored.